Optimizing CO₂ Storage in Saline Aquifers Through Pressure Redistribution in Natuna D-Alpha Field, Indonesia - Roihan Arie Nirwana; Dedy Irawan; Amega Yasutra; Syarif Kamal; Welly Ahmad Ramadan (Scientific Contributions Oil and Gas, 2026)
The increasing concentration  of carbon dioxide (CO₂) in the atmosphere is significantly contributing to the critical exploration of Carbon Capture and Storage (CCS) technology. Although deep saline aquifers offer substantial storage potential for CO2, their effective capacity is often constrained by rapid formation pressure buildup near injector wells and poses safety risks. Therefore, this study aims to propose an integrated strategy to optimize CO₂ storage capacity using pressure redistribution method in a thick carbonate saline aquifer located in Natuna D-Alpha Field, Indonesia. A dynamic numerical simulation is developed by integrating 2D seismic, well logs, core analysis (RCAL/SCAL), and geomechanical parameters derived from log data. The effectiveness of lateral and vertical pressure redistribution is evaluated through brine production wells (PWs) and multi-depth injection, respectively, followed by perforation configuration optimization.Various scenarios are simulated to compare total gas injected and reservoir pressure response against rock fracture limits. The results showed that storage capacity is limited due to the absence of pressure management (Base Case). The implementation of lateral pressure redistribution through brine production proves to be the most significant strategy, capable of increasing storage capacity by approximately 64% of the Base Case in high-rate production scenarios. Furthermore, vertical redistribution strategy using multi-depth injection obtains a 13% capacity increase and improves vertical pressure distribution. A combination of multi-depth injection and brine production shows positive synergy, generating a 44% capacity increase with a storage efficiency of 0.58%. The results also indicate that variations in well perforation geometric patterns (line vs. cross) have minimal impact compared to global pressure management strategies. In line with the analysis, this study finds that brine extraction and vertical injection management are essential to maximizing safe CO₂ storage in thick aquifers.